Comprehensive assessment of pesticide use patterns and increased cancer risk - Gerken, Jacob; Vincent, Gear Thomas; Zapata, Demi; Barron, Ileana G.; Zapata, Isain (Frontiers in Cancer Control and Society, 2024)
Pesticides are an essential feature of modern-day agriculture that adds to the list of factors that increase cancer risk. Our study aims to evaluate comprehensibly this relationship through a population-based approach that considers confounding variables such as county-specific rates of smoking, socioeconomic vulnerability, and agricultural land. We achieved our goal with the implementation of latent class pesticide usage patterns that were further modeled among covariates to evaluate their associations to cancer risk. Our findings demonstrated an association between pesticide usage and increased incidence of leukemia, non-Hodgkin's lymphoma, bladder, colon, lung, pancreatic, cancers, and all cancers combined that are comparable to smoking for some cancer types. Through our comprehensive analysis and unique approach, our study emphasizes the importance of a holistic assessment of the risks of pesticide usage for communities, which may be used to impact future policies regarding pesticides.